THE APPLICATION OF E-BOOK AS A MULTIMEDIA FOR TEACHING READING TO EFL YOUNG LEARNERS AGE 9-10 (RETAIN, 2015)
Reading is one of the important skills that needs to be formed in the process of learning language. However, teaching reading to EFL young learners in Indonesia is different from teaching reading to the native speakers because mostly EFL Young Learners have difficulties in understanding English, especially in reading. Thus, the teachers of EFL Young Learners  need to know how to make them understand English through reading. One of the ways is using media to teach reading. There are many media that can be used to teach reading to EFL young learners, one of them is multimedia e-book. A multimedia e-book consists of some features such as pictures, animations, sounds, and text. The combination of those features is believed tohelp improve students’ understanding. Unfortunately, many teachers still do not know how to use multimedia e-book in teaching reading. Therefore, this study was conducted to describe how the teacher applies the multimedia e-book. Besides, this study was also conducted to know the responses of EFL young learners after being taught using multimedia e-book. A descriptive qualitative research design was used in this study. Interview and observation were used as the instruments to get the data. The results showed that the teacher applied multimedia e-book in sequantial activities namely pre-reading activity, while reading activity and post-reading activity. The students also gave positive responses toward the application of multimedia e-book for teaching reading. Keywords: multimedia e-book, reading, young learners age 9-10.